The views of UK Chinese individuals towards living and deceased-donor kidney transplantation: A qualitative interview study - Matthew Beresford; Katie Wong; Mohammed Al-Talib; Pippa K. Bailey (PLoS ONE, 2025)
The views of UK Chinese people towards transplantation and organ donation are not known. It is not known whether the perspectives of Chinese people living in the UK differ from those of Chinese people living elsewhere in the world, or whether perspectives of UK Chinese people vary according to time spent living in the UK. This qualitative interview study aimed to investigate the views of UK Chinese individuals towards kidney donation and transplantation. It formed part of a convergent parallel mixed-methods programme of research alongside a quantitative registry study which found that UK Chinese individuals experience poorer access to living-donor kidney transplantation compared to UK White individuals. We conducted in-depth semi-structured interviews with sixteen participants across three UK cities. Participants were permanently resident in the UK and self-identified as UK Chinese. Interviews were conducted between 9th April 2020 and 16th July 2020. Interviews were transcribed verbatim, coded using NVivo software, and analysed using inductive thematic analysis. Three main themes and seven sub-themes were identified: (1) Importance of kinship: biological and social (i) Familism, ii) Relationship hierarchy, iii) Matching; (2) Donor sacrifice (i) Negative impact on donors, ii) Bodily integrity after death; and (3) Patient as information gatekeeper (i) Culture of silence, ii) A perceived need for education and engagement. This study provides insights that may offer some explanation for reduced rates of living-donor transplantation amongst UK Chinese individuals. Further research is required to investigate observational research findings not explained here, and to develop effective strategies to improve treatment access for UK Chinese individuals with kidney disease.